Wound healing activities of rafflesia hasseltii extract in rats - Abdulla, M.A.; Ahmed, K.A.; Ali, H.M.; Noor, S.M.; Ismail, S. (The Society for Free Radical Research Japan, 2009)
The effects of topical application of Rafflesia hasseltii buds and flowers extract on the rate of wound healing and histology of healed wound were assessed. Four groups of adult male Sprague Dawley rats were experimentally wounded in the posterior neck area. A thin layer of blank placebo was applied topically to wounds of Group 1 rats. Wounds of experimental animals (Group 2 and 3) were treated with placebo containing 5% and 10% R. hasseltii buds extract, respectively. A thin layer of Intrasite gel was applied topically to wounds of Group 4 animals as reference. Macroscopically, wounds treated with placebo containing 5% and 10% R. hasseltii buds extract or Intrasite gel have been significantly accelerated the rate of wound healing compared to placebo-treated wounds. Histological analysis of healed wounds has confirmed this effect. Wounds treated with placebo containing 5%, 10% R. hasseltii buds extract or Intrasite gel showed markedly less scar width at wound enclosure and granulating tissue contained markedly more collagen and proliferating fibroblasts, but with the absence of inflammatory cells compared to wounds treated with blank placebo. In conclusion, the findings of increased rate of wound closure and contraction together with the histological findingssuggest that Rafflesia hasseltii buds extract is very effective in accelerating the wound healing process.